Pre-existing humoral immunity to low pathogenic human coronaviruses exhibits limited cross-reactive antibodies response against SARS-CoV-2 in children - Li, Nina; Li, XueYun; Wu, Jiani; Zhang, Shengze; Zhu, Lin; Chen, Qiqi; Fan, Ying; Wu, Zhengyu; Xie, Sidian; Chen, Qi; Wang, Ning; Wu, Nan; et al. (Frontiers in Immunology, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection causes asymptomatic or mild symptoms, even rare hospitalization in children. A major concern is whether the pre-existing antibodies induced by low pathogenic human coronaviruses (LPH-CoVs) in children can cross-react with SARS-CoV-2. To address this unresolved question, we analyzed the pre-existing spike (S)-specific immunoglobin (Ig) G antibodies against LPH-CoVs and the cross-reactive antibodies against SARS-CoV-2 in 658 serum samples collected from children prior to SARS-CoV-2 outbreak. We found that the seroprevalence of these four LPH-CoVs reached 75.84%, and about 24.64% of the seropositive samples had cross-reactive IgG antibodies against the nucleocapsid, S, and receptor binding domain antigens of SARS-CoV-2. Additionally, the re-infections with different LPH-CoVs occurred frequently in children and tended to increase the cross-reactive antibodies against SARS-CoV-2. From the forty-nine serum samples with cross-reactive anti-S IgG antibodies against SARS-CoV-2, we found that seven samples with a median age of 1.4 years old had detected neutralizing activity for the wild-type or mutant SARS-CoV-2 S pseudotypes. Interestingly, all of the seven samples contained anti-S IgG antibodies against HCoV-OC43. Together, these data suggest that children's pre-existing antibodies to LPH-CoVs have limited cross-reactive neutralizing antibodies against SRAS-CoV-2.